Determinants of tax noncompliance behaviour among the self-employed in Libya - Abodher, Fareq Mustafa (2019)
Tax noncompliance has become a core issue for many countries around the world, especially developing countries like Libya. The current study empirically examined the moderating effect of political factors on the determinants of tax noncompliance among the Libyan self-employed. In this respect, the political factors (political affiliation and political instability) are more suitable to the political situation of Libya in the wake of the post-2011 revolution that has had major transforming impact on the Libyan economy and society. Data was collected by means of a structured questionnaire designed for the study and distributed to 498 respondents. The PLS-SEM technique was employed to analyse the data and empirically examine the relationship between latent variables. Results showed that Islamic perspective, national pride, tax knowledge, tax penalty and political instability had a significant and positive effect on tax noncompliance whereas tax morale and political affiliation had a significant and negative effect on tax noncompliance among Libyan self-employed. Furthermore, results showed that political affiliation significantly and positively moderates the relationship between Islamic perspective, tax knowledge, tax penalty and noncompliance. However, it significantly and negatively moderates the relationship between national pride, trust in government, tax morale, tax fairness and tax noncompliance. Moreover, political instability significantly and positively moderates the relationship between trust in government, tax morale, tax fairness and tax noncompliance while it significantly and negatively moderates the relationship between Islamic perspective, tax knowledge, tax penalty and tax noncompliance among Libyan taxpayers. Theoretically, the findings have extended the body of knowledge by providing empirical evidence of the moderating effect of political factors on tax noncompliance. Practically, the government should consider these factors as crucial and significant while formulating taxation policies to minimize tax noncompliance's culture among the Libyan self-employed and hence increase government revenues. The recommendation, limitations and direction for future research were also presented.